FORMULATION AND EVALUATION OF LIPOSOMAL GEL FOR TREATMENT OF PSORIASIS. - D. G. UMALKAR; RAJESH K.S (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study was to formulate and evaluate liposomal gel of Diflurasone diacetate for topical application. Liposomes were prepared by using Soya PC and Egg PC by the lipid film hydration method. It was characterized by DSC and Surface morphology of Liposomes by SEM. assessed for particle size, entrapment efficiency, and their effect on in vitro drug release. The Batch B4 containing Soya PC with Cholesterol in 9:1 was found to be optimized .The Stability study of optimized formulation was done as per ICH guidelines. The Optimized liposomes were incorporated into Carbopol gel (2%) and were evaluated for ex vivo drug permeation studies. It was observed that Diflurasone diacetate loaded liposomes bearing hydrogel was more efficient in the treatment of Psoriasis.